Pd-catalyzed regioselective mono-arylation: quinazolinone as the inherent directing group for C(sp(2))-H activation - Garad, Dnyaneshwar N.; Viveki, Amol B.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2017)
The Pd-catalyzed quinazolinone-directed regioselective monoarylation of aromatic rings by C-H bond activation is developed. A broad substrate scope is demonstrated for both quinazolinone as well as diary-liodonium triflates. The use of a base was found to be crucial for this transformation, unlike for the known nitrogen-directed arylations. All of the novel quinazolinones of biological interest were synthesized by using the operationally simple Pd(II)-catalyzed arylation reaction.
Keywords: Aromatic rings; catalysis; Chemical activation; Chemical reactions; Palladium compounds; Regioselectivity